Attachment Style, Early Childhood Trauma, Alexithymia, and Dissociation Among Persons Addicted to Alcohol: Structural Equation Model of Dependencies - Zdankiewicz-Ścigała, Elżbieta; Ścigała, Dawid Konrad (Frontiers in Psychology, 2020)
Aims: Attachment theory is a broadly used paradigm for understanding human affective development. It is recognized that alexithymia is a key factor responsible for the non-adaptive strategies of regulating emotions in people addicted to alcohol. In addition, an important role is attributed to early childhood trauma and dissociation. The theoretical model was examined, in which connections between attachment styles, trauma, and alexithymia and dissociation were investigated in persons addicted to alcohol. Method: The total number of study participants amounted to 268 persons, including 116 women (43% of all subjects) and 152 men (57% of all subjects) at the age of 18–73 (M = 39.19; SD =13.45). In order to measure the analyzed variables, the following questionnaires were applied: MAST, ASQ, TAS-20, TEC, and CES. Results: A comparative analysis between the group of alcohol addicts and non-addicts showed statistically significant differences related to: attachment style, intensity of trauma, alexithymia, and dissociation. With structural equation models (i.e. AMOS, GLS), the adjustment of theoretical model to data was examined, which allowed the description of dependency paths. As a result of the conducted analysis of paths, it was found out that the model was accurately fitted to data, but only when an impact path related to a direct connection between an attachment style and an addiction was deleted. This impact is indirect and, from one side, it results from affective and cognitive deficits, i.e. alexithymia, and on the other side, from the intensity of traumatic experiences. No direct impact of dissociation on the development of an inclination to addiction was found, if contextual variables, i.e. alexithymia and trauma are taken into account. The strongest direct relation was proven in the case of the anxious-ambivalent attachment style and alexithymia (β =0,389;p<0,01), and avoidant attachment style and alexithymia (β = 0,497; p<0,01) which turned out a strong predictor fostering the development of alexithymia and the occurrence of traumas related to emotional negligence, and finally addiction. Conclusions: An extremely important element of the scientific achievement presented here is showing pillars of trauma, alexithymia, dissociation in their cumulative impact on the development of emotional disorders resulting in addiction.